DEVELOPING PHONOLOGICAL AWARENESS AND PRONUNCIATION OF THE FIFTH GRADERS BY USING RHYMING - Mita Elliyuspita (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2017)
Abstract: The objectives of this study were to find out whether or not there was a significant difference in phonological awareness and pronunciation of the fifth graders who were taught by using rhyming poems compared to that of those who were not and to analyze the difficulties encountered by the students in developing their phonological awareness and pronunciation. This was nonequivalent-groups pretest-posttest design. Forty out of 262 fifth graders of SDN 117 Palembang were purposively taken as the samples. The data were analyzed using t-test and questionnaire. The findings showed that there was a significant difference in phonological awareness and pronunciation of the fifth graders who were taught by using rhyming poems compared to that of those who were not. Furthermore, the result of the questionnaire revealed that the students had difficulties in developing their phonological awareness and pronunciation by using rhyming poems. Quick explanation by the writer, too much information and the difficulty of the concepts of phonological awareness were the sources of students’ difficulty.  The findings of this study also found that the students were not accustomed to pronouncing words in English. The pronunciation of English sounds was confusing for them which might be caused by the fact that there are English sounds that do not exist in Bahasa Indonesia.Keywords: phonological awareness, pronunciation, rhyming poems, fifth graders